The effect of thermal aging on solid insulating materials: A case study for dielectric loss and dissipation factor based evaluations under different voltage levels and frequencies. (June 2023) - Akin, Firat; Arikan, Oktay
Highlights: Dielectric performances of PET, HPDE, Presspaper and SBR/NR were investigated during a thermal aging process. The condition of the materials was analyzed by dielectric loss and dissipation factor measurements. Harmonic frequencies and different voltage levels were considered during experiments. The impact of aging on dielectric performances varied for different voltage and frequency levels according to the material type. Abstract: Investigating the dielectric performance phenomenon in insulating materials is critical for condition monitoring and early failure diagnosis. In this study, the effect of thermal aging on dielectric losses and dissipation factors of four insulating materials are investigated: PET, SBR/NR, presspaper and HDPE. A series of measurements at 4 kV and 10 kV with eight different frequencies between 50 Hz and 400 Hz are used to determine the dielectric loss and dissipation factor values of the materials during aging process. Thus, the non-ideal structure of electrical networks and the presence of harmonics are considered. Referring to the results, it is found that the level and frequency of the applied voltage greatly affects the performance of the materials. Also, it is seen that thermal aging have a significant impact on the dielectric properties of the materials. Furthermore, thermal aging effect on the results of different frequencies differs according to the material type.